Dating Methods of Pleistocene Deposits and Their Problems: V. Tephrochronology and Fission-Track Dating - Westgate, John; Briggs, Nancy (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1980)
Summary Much interest and activity is presently centred on the stratigraphie use of tephra. Distinctivetephra layers constitute important time-parallel markers, which if widespread, offer the potential for reliable correlation over long distances. Furthermore, they provide valuable geochrono-logical control for their age can be determined by several radiometric methods. Confident correlations require a multiple criteria approach to tephra characterisation; samples should only be considered equivalent if their stratigraphie, palaeontologic, palaeomagnetic, and radiometric age relations are compatible and the physico-chemical properties ol their glass shards and phenocrysts agree. Special attention should be given to the possibility of resedimentation into a younger stratigraphie position. Because grain-discrete methods of analysis are sensitive to contamination effects, they are to be preferred over those methods that require use of bulk separates. Coarse, proximal tephra can be reliably dated by the K-Ar method as pure mineral separates can be readily isolated, but distal ash-grade tephra is better dated by the fission-track method in which ages are based on tracks counted in individual grains so that detrital contaminants can be easily recognised and avoided. The recent successful application of the fission-track method to distal tephra has resulted in a greatly improved understand-i ng of the late Cenozoic geochronology of areas remote from volcanic centres. Tephrochronology is a useful tool in many areas of Quaternary research; in particular, it will undoubtedly continueto play an important role in the connection of marine and continental sequences, refinement of the palaeomagnetic chronology, calibration of hominid evolution in eastern Africa and other areas, and age-definition of Antarctic and Greenland ice cores.